Phase equilibrium of limonene, p-cymene, indane, butylbenzene and 1,2,3-trimethylbenzene at subatmospheric conditions - Gowda, Rajesh (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.